2023
DOI: 10.1093/eurpub/ckad105
|View full text |Cite
|
Sign up to set email alerts
|

Early substance use disorders and subsequent NEET-not in education, employment or training—a national cohort study

Hélio Manhica,
Diego Yacamán-Méndez,
Hugo Sjöqvist
et al.

Abstract: Background Substance use problems have been associated with poor labour market outcomes. This study investigated whether substance use disorders (SUD) in emerging adulthood increase the likelihood of later being not in employment, education or training (NEET). Methods A national cohort study of 23 5295 males and 227 792 females born between 1981 and 1987. SUD was assessed between ages 17 and 24 years. Logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Alcohol and cannabis are the most commonly used substances in adolescence together with tobacco [ 1 ]. Adolescent substance use is a risk factor for long-term adverse outcomes, such as alcohol and/or substance use disorders [ 2 , 3 ], self-harm [ 4 , 5 ], premature mortality [ 6 , 7 ], and social problems including unemployment [ 8 11 ]. Previous longitudinal studies have also indicated that adolescent substance use has an impact on educational outcomes both in adolescence, but also later in life [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and cannabis are the most commonly used substances in adolescence together with tobacco [ 1 ]. Adolescent substance use is a risk factor for long-term adverse outcomes, such as alcohol and/or substance use disorders [ 2 , 3 ], self-harm [ 4 , 5 ], premature mortality [ 6 , 7 ], and social problems including unemployment [ 8 11 ]. Previous longitudinal studies have also indicated that adolescent substance use has an impact on educational outcomes both in adolescence, but also later in life [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%